Misi Gereja Terhadap Konflik Di Jemaat - Lumi, Falerey; Sarimbangun, Ramli (Educatio Christi, 2024)
This research discusses the paradigm of the church's mission in responding to conflicts in the congregation, especially in the context of the GMIBM Sion Tonom congregation in the Ibolian region. With the problems that occur, it makes the congregation lazy to worship. This thesis aims to provide understanding to congregation members regarding the problems that occur in the congregation and provide understanding for congregation members who are lazy to worship due to conflicts. And in making this thesis using a qualitative method, in which there is a data collection technique carried out. So that it gives good results and the congregation understands the purpose of this research. In this study, it can be concluded that the church is not silent when the members of the congregation are in conflict, here the special servant becomes a mediator as a syalom bearer for the congregation in conflict.